Pengembangan Modul Ajar Pada Mata Kuliah Pendahuluan Fisika Zat Padat Untuk Meningkatkan Penguasaan Konsep Struktur Kristal Bagi Calon Guru - Jannatin `Ardhuha; Aris Doyan; Susilawati Susilawati (Department of Physics Education, Universitas Mataram, 2019)
This study aims at developing teaching module in crystal structure that is suitable to be used at Introduction to Solid State Physics course at the Department of Physics Education, Faculty of Education, University of Mataram. This module was developed by using 4D (define, design, development and disseminate) and its writing technique used a combined compilation and information re-packing technique. Research instruments were crystal structure teaching module, reviewer evaluation sheets on the contents, displays and the language use, as well as students evaluation questionnaire. The teaching module consists of crystal lattice, crystallographic directions and planes, and simple crystal structure. Reviewers respond that the teaching module was of very good category in its contents, display and the use of language. Accordingly, a limited test of the use of this teaching module revealed that this teaching module was of very good category, which denotes that this teaching module was easily understood by students and appropriate to be used. It can be concluded that the teaching module was suitable to be used as supporting material in the Introduction to Solid State Physics course, and it is expected that the use of this teaching module may support students understanding and mastery in crystal structure among pre-service Physics teachers